Ecological status of the Sand River after the discharge of sewage effluent from the Polokwane and Seshego wastewater treatment works - Seanego, Koena Gloria (My University, 2014)
Population growth in urban areas is putting pressure on sewage treatment plants. The improper treatment of sewage entering the aquatic ecosystems causes deterioration of the water quality of the receiving water body. The effect of sewage effluent on the Sand River was assessed. Eight sampling sites were selected, site 1 and 2 were upstream of the of the sewage treatment plant along the urbanised area of Polokwane, whilst sites 3, 4, 5, 6, 7 and 8 were downstream. The physicochemical parameters and coliform counts in the water samples were determined. Macroinvertebrate abundances and diversity (H') was determined at the different sites during the dry and rainy season. The water quality status of the Sand River with respect to the South African scoring system (SASS) scores and average score per taxon (ASPT) was determined. A linear regression was performed to test the correlation of the SASS scores with abundance and H'. Heavy metal concentrations in water, sediment, grass (Ishaemum fasciculatum) and fish (Oreochromis mossambicus) at the sites were evaluated. The suitability of the Sand River and surrounding borehole water for irrigation was also determined. Hierarchical average linkage cluster analysis produced two clusters, grouping two sites above the sewage treatment works and six sites downstream of the sewage effluent discharge point. Principal component analysis (PCA) identified total nitrogen, total phosphorus, conductivity and salinity as the major factors contributing to the variability of the Sand River water quality. These factors are strongly associated with the downstream sites. Canonical correspondence analysis (CCA) indicated that Chironomidae family was found on the nitrogen gradient during the dry season. However during the rainy season, Chironomidae was found in the centre of the ordination which indicated that it was ubiquitous. Escherichia coli levels (1463.73 counts/100ml) in the maturation ponds of Polokwane wastewater treatment works could potentially lead to contamination of the Polokwane aquifer. High diversity was recorded at the sites before discharge and the sites further downstream. There was significant correlation (P<0.05) between the SASS scores and macroinvertebrate diversity during the dry season (R2=0.69) and the rainy season (R2=0.77). Fish samples had significantly higher (P<0.05) iron and copper concentrations, while the vi sediment had significantly higher lead concentration (P>0.05). The United States salinity laboratory (USSL) diagram indicated that the sodium hazard (SAR) and alkalinity hazard (conductivity) was low and the Sand River and borehole water was suitable for irrigation. The residual sodium carbonate (RSC) was below 1.24 meq/l, also indicating that both the Sand River and borehole water is still suitable for irrigation. The total phosphorus concentrations fluctuated across the different site. Total nitrogen concentrations showed a gradual decrease downstream from the point of discharge. The coliform levels also showed a gradual decrease downstream. This shows that the river still has a good self-purification capacity.
Thesis (M.Sc. (Aquaculture)) -- University of Limpopo, 2014
Keywords: Sewage treatment plants; Sewage disposal; Water quality; Sewage.; Sewage disposal in rivers, lakes, etc. -- South Africa -- Limpopo.; Sewage disposal plants -- South Africa -- Limpopo.; Water quality -- South Africa -- Limpopo.